2004
DOI: 10.1002/j.2333-8504.2004.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Procedures for Constrained Adaptive Test Construction

Abstract: The relatively new shadow test approach (STA) to computerized adaptive testing (CAT) proposed by Wim van der Linden is a potentially attractive alternative to the weighted deviation algorithm (WDA) implemented at ETS. However, it has not been evaluated under testing conditions representative of current ETS testing programs. Of interest was whether STA would, under typical high‐stakes on‐demand testing situations, produce tests of comparable or better psychometric quality as those produced by the current weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
2
11
0
Order By: Relevance
“…The finding that the STA worked better than three heuristic methods not only replicates that in van der Linden (2005) in which the STA has been found to outperform the WDM method but also expands to other heuristic methods. This study, however, seemed to suggest this result came at the cost of the STA making the poorest use of items in comparison with the heuristic methods.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…The finding that the STA worked better than three heuristic methods not only replicates that in van der Linden (2005) in which the STA has been found to outperform the WDM method but also expands to other heuristic methods. This study, however, seemed to suggest this result came at the cost of the STA making the poorest use of items in comparison with the heuristic methods.…”
supporting
confidence: 74%
“…The necessity of adjusting the weights in implementing the WDM method has been discussed in a few studies (e.g., Cheng & Chang, 2009;van der Linden, 2005). Our study further underscores the critical role of the choice of and the adjustment of weights in the performance of all three heuristic approaches, in particular, with respect to constraint management.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The shadow test method has been used with the same conditional Sympson‐Hetter method, as well as with an extension of it in which a double‐length shadow test was assembled at each step to create a longer list of items from which the actual item for administration was randomly selected (for details, see Veldkamp & van der Linden, submitted). This extension was used in the study reported by Robin et al (2004). In the empirical study with the adaptive version of the LSAT below, both for the WDM and STA a new item‐exposure control method based on probabilistic item ineligibility constraints was used.…”
Section: Comparison Between Methodsmentioning
confidence: 99%
“…In addition, we evaluate their performances empirically for an adaptive test from a former item pool of the Law School Admissions Test (LSAT). For an empirical case study with an adaptive test in use at Educational Testing Service (ETS), see Robin, van der Linden, Eignor, Steffen, and Stocking (2004). The differences between this case study and the empirical evaluation in this article are explained below.…”
Section: Fictitious Item Pool With Five Items With Three Different mentioning
confidence: 99%